2021
DOI: 10.1111/ffe.13418
|View full text |Cite
|
Sign up to set email alerts
|

Williams expansion utilized for assessment of crack behaviour under mixed‐mode loading in alkali‐activated fine‐grained composite

Abstract: The paper concerns an experimental study on the crack deflection angle in a semi‐circular disc made of an alkali‐activated fine‐grained composite under mixed‐mode conditions. This study is supplemented by an extensive numerical analysis that calculates the crack deflection angles via generalized (multi‐parameter) fracture criteria. It is proved that the use of higher‐order terms of the Williams expansion for the approximation of the crack‐tip stress field leads to more accurate results. The influence of variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The results presented in this article were used as valuable input parameters of material models used for numerical simulations of crack propagation in the semi-circular specimens loaded under mixed-mode I/II conditions. The results of numerical simulations were used for the verification of experimentally obtained data and were presented in a separate article [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results presented in this article were used as valuable input parameters of material models used for numerical simulations of crack propagation in the semi-circular specimens loaded under mixed-mode I/II conditions. The results of numerical simulations were used for the verification of experimentally obtained data and were presented in a separate article [17].…”
Section: Discussionmentioning
confidence: 99%
“…Note that numerical simulation was performed prior to the experimental verification to suggest different geometrical configurations with various mixed-mode I/II conditions (to cover as wide a range of mixed-mode levels as possible) and to design the experiment. The detailed information can be found in a separate article, which is currently under consideration for publication [17]. The numerical modeling of the fracture initiation and propagation in quasi-brittle materials has been developed for several decades.…”
Section: Introductionmentioning
confidence: 99%
“…While majority of research studies are dedicated to the evaluation of the coefficient of the singular term, [11][12][13][14][15][16] some recent studies have highlighted the importance of first non-singular term in the accurate assessment of stress distribution around bi-material notches. For instance, Mirsayar et al 17 and Malíkov a et al 18 demonstrated the considerable role of first non-singular term in fracture initiation angle in bi-material and composite notches. Ayatollahi et al 19 utilized the photoelastic method accompanied by the least-squares technique to evaluate the coefficients of singular and higher order terms (HOTs).…”
Section: Introductionmentioning
confidence: 99%